The effects of pegylated interferon alpha 2b on bile-duct ligation induced liver fibrosis in rats - (:unkn) unknown (MEXICAN ASSOC HEPATOLOGY, 2009)
Objective. To test the effects of peginterferon in an unrecoverable model of bite-duct ligation (BDL) induced liver fibrosis. Material and methods. Thirty-seven Wistar rats were divided into five groups: group 1, BDL + peginterferon (n = 8); group 2, BDL (n = 8); group 3, sham + peginterferon (n = 7); group 4, sham (n = 7); and group 5, control group (n = 7). Peginterferon-alpha 2b (50 mu gr/kg) or saline (1 mL/kg) was administered intraperitonealy every week for four weeks. Serum biochemical markers, liver tissue oxidative stress, collagen and transforming growth factor-beta (TGF-beta) levels were examined after four weeks. Liver slides were stained by hematoxylin and eosin and Masson trichrome\Gomory reticulum staining. Results. The levels of tissue collagen, TGF-beta, biochemical markers (AST, ALT, bilirubins, alkaline phosphates, gamma-glutamyl transpeptidase) and oxidative stress markers (Malondialdehyde, luminal, lucigenin) of the BDL group were higher than the sham operated and control groups (all-p < 0.001). Peginterferon improved malondialdehyde, luminal and glutathione levels in the BDL + peginterferon group (p < 0.05). Histopathological examination of the BDL groups showed stage-3 fibrosis, white all, the control groups were normal. Peginterferon showed no improvement in fibrosis either histologically, or biochemically. Conclusions. Peginterferon improved levels of malondialdehyde, glutathione and luminal in the rat model of BDL induced liver fibrosis. Peginterferon however, showed no anti-fibrotic effects in this model, and therefore may not be a useful treatment for liver fibrosis.
Keywords: Peginterferon; Bite duct Ligation; Cirrhosis; Liver fibrosis; Collagen; Transforming growth factor beta; Malondialdehyde; Glutathione; Luminal; Lucigenin; CHRONIC HEPATITIS-C; FIBROGENESIS SERUM MARKERS; CHRONIC VIRAL-HEPATITIS; HISTOLOGICAL ACTIVITY; OXIDATIVE STRESS; ALPHA-INTERFERON; DRUG-METABOLISM; REACTIVE OXYGEN; SCORING SYSTEM; STELLATE CELLS